AB0532 CORRELATION WITH THE FREQUENCY OF DISEASE RELAPSES DURING THE FIRST 3 YEARS FROM THE DIAGNOSIS AND DISEASE OUTCOMES IN BEHCET'S SYNDROME. (2nd June 2020) - Talarico, R.; Figliomeni, A.; Mione, L.; Parma, A.; Cioffi, E.; Mosca, M.
Abstract : Background: Beside the organ involvement, a number of demographic factors could considerably influence the long-term and short-term outcomes of Behçet's syndrome (BS): age at disease onset, duration of disease, gender and sex. Younger men patients are more suitable to have a more severe disease, due to an increased frequency both of morbidity and mortality, related to ocular, vascular and neurological involvement Objectives: The primary aims of the study were to evaluate disease activity in a cohort of BS patients consecutively followed in a BS clinic of a tertiary centre and to explore whether there is a correlation between frequency of relapses in the first 3 years of diseases and disease outcomes. Methods: One-hundred and sixty-five patients (91 males and 74 females; mean age 39±9 years, mean disease duration 9±5) with a diagnosis of BS according to the ISG criteria were studied. Disease activity has been evaluated by BDCAF and patients were also categorized in major or minor involvement of BS according or not to the presence of ocular, neurological and vascular involvement in the course of disease The numbers of relapses in the first 3 years from diagnosis were correlated with disease outcome and damage. Results: At time of the evaluation, 47% of BS patients presented an active disease; 69 patients presented muco-cutaneous involvement, 39 ocular disease, 21 joint involvement, 12 neurological impairment and 9 gastro-enteric involvement. Seventy-nine percent of patients presented in the course of the disease a severe BS involvement and the majority was represented by patients characterised by a more frequent relapse in the first 3 years of disease (M/F: 65/48, mean age 43±3 years). Those patients who experienced a more higher number of relapse in the first 3 years compared to the others were also characterised by poor disease outcomes and worse prognosis over time and this correlation was independent by the therapies taken. Conclusion: The high frequency of relapses during the first three years from diagnosis may be considered an important prognostic factor for disease outcome in BS patients, therefore could be taken into account as a useful element to tailor the management, not only according to the type and severity of symptoms and epidemiological factors. Acknowledgments: none Disclosure of Interests: None declared